2012
DOI: 10.5392/jkca.2012.12.01.338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catechins on Serum Lipids in Obese Women

Abstract: Twenty-seven obese women were participated in this study. Eight women were tea catechin drinking group, Nine women were exercise group, and ten women were tea catekin drinking-combined with exercise group. After catechin drinking or exercise conducted, blood lipid factor were analyzed. body weight and triglycerides low density lipoprotein cholesterol levels were significantly decreased in tea catekin drinking combined with exercise group (p<0.001) and exercise group (p<0.001). total cholesterol were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…A study by Victoria [ 39 ] showed that no significant effect of green tea on BMI (SMD = −0.22, CI −0.52 to 0.074, p = 0.14) was observed with a heterogeneity of 69.7 % (p < 0.001) whereas a significant effect of green tea on body weight (SMD = −0.7, CI −1.16 to −0.23, p = 0.003) was observed with a heterogeneity of 86.4 % (p < 0.001). At the same time, a study in Korea [ 40 ], found that catechin drink intake has no significant effect on the weight in obese women, However, combining with exercise or exercise only can effectively improve the weight of obese women, which is consistent with the present study. It showed that green tea catechin supplementation in the overweight and obese population did not show significant effect on body weight.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Victoria [ 39 ] showed that no significant effect of green tea on BMI (SMD = −0.22, CI −0.52 to 0.074, p = 0.14) was observed with a heterogeneity of 69.7 % (p < 0.001) whereas a significant effect of green tea on body weight (SMD = −0.7, CI −1.16 to −0.23, p = 0.003) was observed with a heterogeneity of 86.4 % (p < 0.001). At the same time, a study in Korea [ 40 ], found that catechin drink intake has no significant effect on the weight in obese women, However, combining with exercise or exercise only can effectively improve the weight of obese women, which is consistent with the present study. It showed that green tea catechin supplementation in the overweight and obese population did not show significant effect on body weight.…”
Section: Discussionsupporting
confidence: 91%